Winchester Cathedral
The character of Early English work is quite distinct in this fine entrance and vault of one of the chapels built behind the Norman choir at Winchester. Most of the medieval color, together with the glass, was removed from English cathedrals, and the extent to which the painting formed a part of the architecture has only been recognized in recent years. Much color was restored during the nineteenth century with Victorian enthusiasm.